Sexuality and heart [Cinsellik ve kalp] - (:unkn) unknown (My University, 2004)
Sexual dysfunction prevalence is considerably high in both male and female cardiovascular patients. Hypertension, hyperlipidemi, obesity and habit of smoking etc. are factors that pose risks for not only cardiovascular disease but also for sexual dysfunction. However, there are no concrete evidences to prove that sexual activities alone are causes for acute cardiac events. It is noted in related studies that patients, following an MI, are hindered from sexual activities for the fear of undergoing another MI or due to the existence of angina. Therefore, it is very important that the patients with MI be educated on sexual activities prior to discharge.